Pembelajaran Seni Lukis Menggunakan Cat Akrilik dengan Teknik Plakat di Kelas VIII Ignatius Global School Palembang: Penelitian - Rika Dwi Oktavia; Dedy Firmansyah; Silo Siswanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study is the background of the importance of understanding how painting teachers integrate acrylic paint techniques in the learning process. This study aims to explore how the strategies used in teaching are used by teachers and their impact on students in painting. So this study is entitled